The freedom and power of forgiveness - MacArthur, John F. 1939- (Wheaton, IL Crossways, 1998)
Includes bibliographical references and indexes.
Donated by Dr Keith Graham, Principal of Emmaus Bible College 1991-1998, June 1998.
Keywords: Forgiveness -- religious aspects -- Christianity